Egocentric and Allocentric Spatial Memory in Korsakoff’s Amnesia - Janzen, Gabriele; van Roij, Claudette J. M.; Oosterman, Joukje M.; Kessels, Roy P. C. (Frontiers in Human Neuroscience, 2020)
The goal of the present study was to investigate spatial memory in a group of patients with amnesia due to Korsakoff’s syndrome. We used a virtual spatial memory task that allowed to separate the use of egocentric and allocentric spatial reference frames to determine object locations. Research investigating the ability of patients with Korsakoff’s amnesia to use different reference frames are scarce and it remains unclear whether these patients are impaired in using ego- and allocentric reference frames to the same extent. Twenty Korsakoff patients and twenty-four matched controls watched an animation of a bird flying in one of three trees standing in a virtual environment. After the bird disappeared, the camera turned around, by which the trees were briefly out of sight and then turned back to the centre of the environment. Participants were asked in which tree the bird was hiding. In half of the trials, a landmark was shown. Half of the trials required an immediate response whereas in the other half a delay of 10 seconds was present. Patients performed significantly worse than controls. For all participants trials with a landmark were easier than without a landmark and trials without a delay were easier than with a delay. While controls were above chance on all trials patients were at chance in allocentric trials without a landmark present and with a memory delay. Patients showed no difference in the ego- and the allocentric condition. Together the findings suggest that despite the amnesia, spatial memory and especially the use of ego- and allocentric references frames in Korsakoff patients is spared.